Employee Recruitment in Islamic Perspective (Analysis of Employee Recruitment Process at Waroeng Steak & Shake) (TAWAZUN: Journal of Sharia Economic Law, 2022)
This study aims to recruit employees at Waroeng Steak & Shake in an Islamic perspective. This research on employee recruitment in an Islamic perspective is carried out using a qualitative approach with the type of field research (field research) with data collection techniques using Interview, Observation and Documentation. The results showed that the employee recruitment process carried out by Waroeng Steak & Shake was carried out based on Islamic principles both sourced from the Qur'an or Hadith. In the employee recruitment process, Waroeng Steak & Shake emphasizes competence and integrity. In Islam, competence and integrity can be reflected in religious competence (quwwah al-din), expertise (quwwah al-ahliyah), work ethic (quwwah fikr wa ruhiyah), and trustworthiness.